Human Resource and Contract Management in the Public School: A Legal Perspective - Marczely, Bernadette; Marczely, David William (Rowman & Littlefield Publishers, 2002)
Human resource management, an essential part of public school administration, is particularly vulnerable to legal interpretation and challenge. Like all other institutions that receive federal funds, public schools have a unique rulebook that sets the parameters for management, particularly with respect to human resource issues. This authoritative text is an essential resource for administrators. It will help new and experienced managers to navigate the practical and legal concerns likely to affect the many human resource functions including recruiting, hiring, and firing personnel; collective bargaining; staff development; and record keeping and reporting. The insightful discussion of the laws and policies currently structuring human resource management is augmented with examples of forms and procedures to be used in addressing particular hr functions. An Instructor's Manual has been developed to accompany this text.